2015
DOI: 10.13005/ojc/320237
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity of the Extracts from Jatropha curcas Fruit and Its Correlation with Total Phenolic Content

Abstract: The correlation between antioxidant activity and total phenolic content of the crude extract from J. curcas fruit were evaluated. The crude extract was obtained by extracting with selected solvent and fractionated with a hydrophilic lipophilic balanced (HLB) cartridge. The total phenolic content of crude extract with Folin-Ciocalteu method gave the content at 7.04 ± 0.10 mg GAE/g of extract and 0.22-18.61 mg GAE/g of extract for its fraction. The antioxidant activity of crude extract was 270.98 ± 0.59 µmol Fe/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
1
2
0
1
Order By: Relevance
“…The leaves of J. curcas may therefore possess higher antioxidant activity than the seeds of J. curcas. This is in line with the findings of 26 , who reported that increasing antioxidant activity correlate with total phenolic content of J. curcas fruits.…”
Section: Resultssupporting
confidence: 93%
“…The leaves of J. curcas may therefore possess higher antioxidant activity than the seeds of J. curcas. This is in line with the findings of 26 , who reported that increasing antioxidant activity correlate with total phenolic content of J. curcas fruits.…”
Section: Resultssupporting
confidence: 93%
“…For instance, investigation of the methanolic extracts of J. gossypiifolia revealed the leaves to have higher total phenolic content (65.66 mg GAE/g) compared to the stem portion (33.332 mg GAE/g) [ 21 ]. Additionally, the total phenolic content of crude extract J. curcas fruit was found to possess TPC 7.04 ± 0.10 mg GAE/g of extract and 0.22–18.61 mg GAE/g of extract for its fraction [ 22 ]. The polyphenolic contents of the ethanol, methanol and aqueous extracts of the stem bark of J. curcas were also assessed by Igbinosa, et al [ 23 ], whereby the total phenol and total flavonoid were obtained in amounts of 10.92–28.87 mg tannic acid/g extract and 6.28–11.18 mg quercetin/g extract, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, in the study of Saosoong, Litthanapongsatorn and Ruangviriyachai [ 22 ], the antioxidant activity of the crude extract of J. curcas fruit was found to be 270.98 ± 0.59 μmol Fe/g of extract using the phenanthroline method, while the extract gave an IC 50 of 14.09 ± 0.05 mg/mL with the DPPH method. In particular, the methanolic fraction showed the highest antioxidant activity with an IC 50 of 0.04 ± 0.02 mg/mL with the DPPH method and an antioxidant activity of 207.53 ± 2.58 μmol Fe/g of extract with the phenanthroline method.…”
Section: Resultsmentioning
confidence: 99%
“…These results agree with Kavallieratos et al (2023), who reported that in grains treated with J. curcas L. oil (Euphorbiaceae), there was a lower emergence of S. oryzae and Ephestia küehniella Zeller (Lepidoptera: Pyralidae) compared with untreated grains. The high concentration of phenol ester in the seeds may explain the superior biocidal activity of J. curcas oil extracts (Saosoong et al, 2016). Application of the extracts directly was more efficient since extract molecules are absorbed by insects' integuments, affecting their central nervous system and leading to their death (Ubulom et al, 2021).…”
Section: Discussionmentioning
confidence: 99%